Experimental behaviour of base plate joints equipped with self‐centering system and friction dampers. (13th September 2017) - Santiago, A.; da Silva, L. Simoes; da Silva, L.C. Fernandes; Cavallaro G., Ferrante; Francavilla, A.; Latour, M.; Piluso, V.; Rizzano, G.
ABSTRACT: A FREE from DAMage friction connection is a connection where friction dampers are introduced by adding friction pads, sliding on slotted steel plates, pre‐stressed with high strength bolts. Even though such a technology provides great advantages in terms of removal of damage to the structural elements, it has the main drawback to provide a limited re‐centering capability. In fact, during a seismic loading history, FREEDAM joints rotate concentrating the dissipation in the friction interface but, due to their high stiffness, after the end of the ground motion, they remain in a deformed position, leaving also the structure with residual drifts resulting in out‐of‐plumbs. The goal of the work is to propose an approach to provide FREEDAM structures with a self‐centering capacity by studying particular devices, to be installed in beam‐to‐column joints or column base joints. In this paper, the attention is focused on the problem of re‐centering of base plate joints studying a detail consisting in a connection located at the base of the columns of the first storey equipped with friction dampers and threaded bars. The threaded bars work as elastic springs thanks to sets of Belleville washers used to increase the deformability and to allow the opening of a gap in the connection. The main breakthrough of the proposed technology with respect to the existing literature, aside from the methodology employed for the design of the friction connection, is that the self‐centering capability is obtained with re‐centering elements (threaded bars and Belleville springs) which are not conceived to be extended up to the end of the column at the top storey of the building, but they have a size similar to the column splice's cover plates. The work reports the results of a preliminary experimental investigation on this joint detail which has regarded cyclic and pseudo‐dynamic tests. The experimental results presented seems very encouraging towards the possible development of base plate joints with self‐centering capacity combined with friction dampers.